Sistem Pendukung Keputusan Pemilihan Asisten Laboratorium Menggunakan Metode MABAC - Rili Aditya; Satrio Apriza Pradana; Wahyudi Maulana; Divi Handoko; David David (LKP Unity Academy, 2025)
The selection of the right laboratory assistant is very important to support practicum activities in the laboratory. The complex selection process requires a systematic approach to assessing candidates based on various criteria, such as GPA, semester specialty, programming knowledge test, interview test. The Multi-Attributive Border Approximation Area Comparison (MABAC) method is one of the methods in multi-criteria decision-making that can be used to solve this problem. MABAC offers an effective approach to evaluating and ranking candidates based on the weight of predetermined criteria. This study implements the MABAC method in SPK for the selection of laboratory assistants, with the aim of improving objectivity and accuracy in the selection process. The results of this system show that MABAC is able to provide consistent and reliable recommendations in determining the most suitable candidates as laboratory assistants.